Exploring the environmental sustainability through customers’ acceptance: voices of the prospects of eco-friendly menstrual products (EFMP) in Malaysia - Omar, Norhazlina; Maulan, Suharni; Mhd Sarif, Suhaimi (Universiti Islam Selangor (UIS), 2025)
Solid waste in Malaysia is facing an issue of the increment of the daily collected solid waste. One of the methods to settle this problem is by encouraging the use of eco-friendly menstrual product (EFMP). The objective of this research is to understand of Environmental Sustainability through the customers’ acceptance: voices of the prospects of Eco-Friendly Menstrual Products (EFMP) in Malaysia. Observation has been done in two main supermarkets in Malaysia with in-depth, face to face interview among five women in Klang Valley area. The Findings shows that the prospects are lacking about the awareness of EFMP. Also, the factors affecting the encouragement of the prospects to use EFMP are the awareness, products, environmental concern, subjective norms, perceived behavioural control, menstruation and price. In conclusion, EFMP is something new in the market where the managers and policymakers has to be more creative in introducing and encouraging the usage of EFMP